ANALISIS DAMPAK PENDIDIKAN MULTIKULTURAL DALAM MENCEGAH PERILAKU BULLYING DI SEKOLAH DASAR - Aam Ambarwati; Ahmad Rifqy Ash-Shiddiqy; Ai Sartika Dewi; Elis Nur Astuti; Susi Ardiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the impact of multicultural education in preventing bullying behavior in Elementary Schools. The research method used is a literature study of 10 relevant articles. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. Based on the literature study, it can be concluded that multicultural education has proven effective in reducing bullying behavior in Elementary Schools. Bullying cases in Elementary Schools are very concerning, not only physically hurting but bullying can disturb the victim's psyche which will have an impact until adulthood. Therefore, the role of schools in preventing bullying is very important. Through multicultural education, students' attitudes of tolerance and empathy develop so that they are better able to respond to social conflicts peacefully. The role of teachers is not only to master and realize learning activities, but teachers must be able to instill the core values ​​of multicultural education such as democracy, humanism and pluralism and instill good character in students so that the school environment becomes a safe place free from bullying.